Dialog. - Kunstpalast, Düsseldorf; Wilhelm-Lehmbruck-Museum, Duisburg; Centrum Sztuki, Warschau (Düsseldorf : Kunstmuseum Düsseldorf, 1989)
Kiffl, Erika ; Balka, Miroslaw ; Berke, Sybille ; Jaworski, Halina ; Pawlak, Wlodzimierz ; Przybyla, Joanna ; Simon, Klaus ; Tarasewicz, Leon ; etc.
Dialog, Kunstpalast, Düsseldorf, 16.9.1989 - 1.10.1989 / Wilhelm-Lehmbruck-Museum, Duisburg, 15.10.1989 - 19.20.1989 / Centrum Sztuki, Warschau, 2. April bis ende April 1990
boek